A train to impossible places adventure delivery to the lost city / P.G. Bell; illustrated by Flavia Sorrentino - Bell, P. G. (Peter Gwilym) (Train to impossible places, 2021)
When the Impossible Postal Express is charged with returning an overdue library book, Suzy Smith looks forward to a nice, simple delivery--just the thing she needs to convince her anxious parents to let her keep her job on the train. So shes less than thrilled to discover that not only is the book alive, it's full of a growing and dangerous magic. Worse still, the world to which it belongs is missing, and Suzy and her friends will have to use all their ingenuity to find it. Suzy must help a fledgling rebellion seize power, return the book to its rightful owner, and get home before her parents ground her for life.